8
$\begingroup$

How to find the sum of the following series

$$\frac{1}{5} - \frac{1\cdot 4}{5\cdot 10} + \frac{1\cdot 4\cdot 7}{5\cdot 10\cdot 15} - \dots\,.?$$

I have no idea. I have written the general term and tested its convergence by Gauss' test for convergence, but they are neither the question nor the answer.

$\endgroup$
  • $\begingroup$ Could you reveal what your general term is? It is not clear what the pattern in "1, 4, 7, ..." is supposed to be. $\endgroup$ – Henning Makholm Jan 12 '14 at 2:39
  • 1
    $\begingroup$ The general term is $$\frac{(-1)^{n-1}}{5^n}. \frac{1.4.7. \dots (3n-2)}{n!}$$. $1, 4, 7,\dots$ is in an AP. What to do after it? $\endgroup$ – Dutta Jan 12 '14 at 2:45
  • $\begingroup$ See binomial series. $\endgroup$ – Lucian Jan 12 '14 at 3:02
8
$\begingroup$

From the Generalized Binomial Theorem (for $|x|<1$), $$\left(1+x\right)^n=1+nx+\frac{n(n-1)}{2!}x^2+\frac{n(n-1)(n-2)}{3!}x^3+\cdots$$

Method $1:$

$\displaystyle -\frac{1\cdot 4\cdot 7}{5\cdot 10\cdot 15}=\frac{-\frac13\left(-\frac13-1\right)\left(-\frac13-2\right)3^3}{3!\cdot 5^3}=\frac{-\frac13\left(-\frac13-1\right)\left(-\frac13-2\right)}{3!}\left(\frac35\right)^3 $

and $\displaystyle \frac{1\cdot 4}{5\cdot 10}=\frac{-\frac13\left(-\frac13-1\right)3^2}{2!\cdot 5^2}=\frac{-\frac13\left(-\frac13-1\right)}{2!}\left(\frac35\right)^2$

and $\displaystyle-\frac15=\left(-\frac13\right)\left(\frac35\right)$

So, the given series $\displaystyle=1-\left(1+\frac35\right)^{-\frac13}$


Method $2:$

If $\displaystyle nx=-\frac15 \ \ \ \ (1)$

and $\displaystyle\frac{n(n-1)}{2!}x^2=-\frac{1\cdot4}{5\cdot10}=\frac2{25} \ \ \ \ (2)$

Divide $(2)$ with the square of $(1)$ to get $n$ and then $x$ using $(1)$

and check that $x,n$ satisfies $\displaystyle\frac{n(n-1)(n-2)}{3!}x^3=-\frac{1\cdot 4\cdot 7}{5\cdot 10\cdot 15}$

$\endgroup$
  • $\begingroup$ @HopelessFool, how about this method? $\endgroup$ – lab bhattacharjee Jan 12 '14 at 5:39
  • $\begingroup$ Higher Secondary mathematics. Half forgotten. My fault no doubt. I do not understand why these are asked in NBHM! Thank you. $\endgroup$ – Dutta Jan 12 '14 at 6:08
8
$\begingroup$

For any $\gamma \in \mathbb{R}$ and $k \in \mathbb{N}$, let $(\gamma)_k = \gamma(\gamma+1)\cdots(\gamma+k-1)$ be the rising Pochhammer symbol. Using following expansion $$\frac{1}{(1-z)^\gamma} = \sum_{k=0}^\infty \frac{(\gamma)_k}{k!} z^k$$ We can evaluate the sum as

$$\sum_{k=1}^\infty (-1)^{k-1}\frac{\prod_{j=0}^{k-1}(3j+1)}{5^kk!} = - \sum_{k=1}^\infty \frac{(\frac13)_k}{k!}\left(-\frac{3}{5}\right)^k = 1 - \frac{1}{\sqrt[3]{1+\frac{3}{5}}} = 1 - \frac{\sqrt[3]{5}}{2} $$

$\endgroup$
1
$\begingroup$

According to Maple, $$ \sum_{m=0}^\infty (-1)^m \dfrac{\prod_{j=0}^m (1+3 j)}{\prod_{j=0}^m (5 + 5 j)} = 1 - \dfrac{5^{1/3}}{2}$$

$\endgroup$
  • $\begingroup$ Dear Sir, I do not know Maple. The left hand side is the general term written differently. How to get the the left hand side by manual computation? $\endgroup$ – Dutta Jan 12 '14 at 2:56

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.